Potential for Meaning Making in Mathematics Textbooks - Norberg, Malin (Designs for learning, 2019)
A Multimodal Analysis of Subtraction in Swedish Year 1   Textbooks are a common teaching tool widely used in children’s mathematical education. Comparative studies of textbooks have focused on different aspects, such as content, mathematical symbols and so on. However, a multimodal approach to textbook research—that is, studying how writing, images, mathematical symbols, etc. interact—is sparse. This study analyses 40 exercises from 17 Swedish Year 1 (children 7–8 years) textbooks using a multimodal approach with a focus on subtraction as an arithmetic operation. The aim was to describe and analyse how subtraction in Swedish Year 1 mathematics textbooks can be understood using a multimodal approach. The results show that it is sometimes possible to solve an exercise without focusing on the mathematical content that the exercise is designed to offer. Writing, images, mathematical symbols, speech and moving images are used differently within the same textbook and between textbooks. The results also show that there are considerable similarities between the exercises in printed and digital textbooks, with some exceptions. The examples in the study indicate that three different approaches are needed when working with these exercises, which implies great complexity in children’s meaning making in their work with mathematics textbooks. This could negatively impact children’s access to beneficial learning situations. Therefore, this study could contribute to a larger awareness of the complexity in question, which, by extension, may contribute to the development of beneficial learning situations in mathematics education, especially regarding subtraction.